Unravelling the complete mitochondrial genomes of Thrips tabaci Lindeman and Thrips parvispinus Karny (Thysanoptera: Thripidae) and their phylogenetic implications - Soumia, P.S.; Shirsat, Dhananjay V.; Karuppaiah, Vadivelu; Divekar, Pratap A.; Mahajan, Vijay (Frontiers in Insect Science, 2025)
Onion (Allium cepa Linnaeus) is an important vegetable crop valued for its nutritional properties and economics worldwide. Onion cultivation faces serious threats from pests and diseases, particularly onion thrips (Thrips tabaci), which cause substantial yield losses. Recently, Black thrips (Thrips parvispinus), an invasive key pest of chili, have been reported to cause severe damage in onion crop and is likely to devastate the onion cultivation in near future. Therefore, this study was conducted to address the knowledge gap concerning the genetic basis and evolutionary history of T. tabaci and T. parvispinus through sequencing of their mitochondrial genomes. T. tabaci and T. parvispinus were collected from different locations in Maharashtra, India, and reared in the laboratory. The mitochondrial genomes of T. tabaci and T. parvispinus were sequenced to a length of 15,277 and 15,285 bp, respectively. Both genomes exhibited similar gene organization with regard to thirteen protein-coding genes and two rRNA genes. T. tabaci contained 19 tRNA genes whereas T. parvispinus contained 18 tRNA genes. The evolutionary positions of T. tabaci and T. parvispinus within the Thysanoptera order were elucidated through phylogenetic analysis of the mitogenomes of 15 thrips species. These findings provide crucial insights into the genetic makeup and evolutionary dynamics of both the thrips species, thereby aiding the development of novel and sustainable pest management strategies to mitigate their impacts on crops in the changing climate scenario.